A Criminal Procedure Regime Based on Instrumental Values. Book Review Of: About Guilt and Innocence: The Origins, Development, and Future of Constitutional Criminal Procedure. by Donald A. Dripps - Maclin, Tracey (2005)
Book review: About Guilt and Innocence: The Origins, Development, and Future of Constitutional Criminal Procedure. By Donald A. Dripps. Praeger Publishers. 2003. xix + 295 pp. Reviewed by: Tracey Macli